2009
DOI: 10.1103/physreva.79.062517
|View full text |Cite
|
Sign up to set email alerts
|

Ground state of two electrons on a sphere

Abstract: We have performed a comprehensive study of the singlet ground state of two electrons on the surface of a sphere of radius R. We have used electronic structure models ranging from restricted and unrestricted Hartree-Fock theory to explicitly correlated treatments, the last of which lead to near-exact wavefunctions and energies for any value of R. Møller-Plesset energy corrections (up to fifth-order) are also considered, as well as the asymptotic solution in the large-R regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 51 publications
4
91
0
Order By: Relevance
“…We will use the term "spherium" to describe this system. In recent work [19], we examined various schemes and described a method for obtaining near-exact estimates of the 1 S ground state energy of spherium for any given R. Because the corresponding Hartree-Fock (HF) energies are also known exactly [19], this is now one of the most complete theoretical models for understanding electron correlation effects.In this Letter, we consider D-spherium, the generalization in which the two electrons are trapped on a D-sphere of radius R. We adopt the convention that a D-sphere is the surface of a (D + 1)-dimensional ball. (Thus, for example, the Berry system is 2-spherium.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We will use the term "spherium" to describe this system. In recent work [19], we examined various schemes and described a method for obtaining near-exact estimates of the 1 S ground state energy of spherium for any given R. Because the corresponding Hartree-Fock (HF) energies are also known exactly [19], this is now one of the most complete theoretical models for understanding electron correlation effects.In this Letter, we consider D-spherium, the generalization in which the two electrons are trapped on a D-sphere of radius R. We adopt the convention that a D-sphere is the surface of a (D + 1)-dimensional ball. (Thus, for example, the Berry system is 2-spherium.)…”
mentioning
confidence: 99%
“…We will use the term "spherium" to describe this system. In recent work [19], we examined various schemes and described a method for obtaining near-exact estimates of the 1 S ground state energy of spherium for any given R. Because the corresponding Hartree-Fock (HF) energies are also known exactly [19], this is now one of the most complete theoretical models for understanding electron correlation effects.…”
mentioning
confidence: 99%
“…Taking (3) as a zeroth-order wave function, one can use standard perturbation theory methods [43] to show that the small-R (weak correlation) expansion of the ground- We have demonstrated that, for each value of the angular momentum J, one is able to obtain polynomial and irrational solutions for both the singlet and triplet manifolds. The latter are degenerate but exhibit different geometric (Berry) phase behavior.…”
mentioning
confidence: 99%
“…26,34 The non-interacting orbitals for an electron on a sphere of radius R are the normalized spherical harmonics Y m (Ω), where Ω = (θ, φ) are the polar and azimuthal angles respectively. We will label spherical harmonics with = 0, 1, 2, 3, 4, .…”
Section: Electrons On a Spherementioning
confidence: 99%